Unveiling Model Superiority: A Comprehensive Analysis of Deep Learning Architectures for Robust Breast Cancer Prediction and Generalization - Wagdy, Ahmed (International Journal of Computer Sciences and Engineering, 2025)
Breast cancer remains a leading global health challenge, demanding early, accurate, and interpretable diagnostic tools. This study presents a comprehensive evaluation of five pretrained convolutional neural networks—DenseNet121, InceptionV3, VGG19, EfficientNetB4, and MobileNetV3—for classifying breast ultrasound images from the BUSI dataset into Normal, Benign, and Malignant categories. The proposed framework integrates transfer learning, advanced preprocessing techniques, and class-weighted optimization to enhance model generalization and address data imbalance. Unlike prior studies, this work introduces a multi-model statistical comparison using Paired T-test, Wilcoxon Signed-Rank, and Cohen’s d, along with real-time inference benchmarking and a deployment-ready performance dashboard. Among the evaluated models, DenseNet121 demonstrated superior performance with an accuracy of 89.92% and an AUC-ROC of 0.95, outperforming existing state-of-the-art methods on the BUSI dataset. InceptionV3 also achieved strong results with 87.84% accuracy and notable inference speed. The findings confirm the clinical viability of integrating statistical rigor, inference-time awareness, and visual interpretability into deep learning pipelines for breast cancer detection. This framework lays the groundwork for scalable, explainable, and deployment-focused diagnostic AI systems in medical imaging.